Dobutamine-Induced Strain and Strain Rate Predict Viability Following Fibrinolytic Therapy in Patients with ST-Elevation Myocardial Infarction - Ismail, Mohamed; Nammas, Wail (Frontiers in Cardiovascular Medicine, 2015)
Background: Low-dose dobutamine stress echocardiography is increasingly used for identifying myocardial viability. Aim: We explored whether dobutamine-induced strain (S) and strain rate (SR) can identify myocardial viability following fibrinolytic therapy for ST-segment-elevation myocardial infarction (STEMI), taking 99mTc-sestamibi scintigraphy as the 'gold standard' for diagnosis. Methods: We enrolled 60 consecutive patients presenting for myocardial viability assessment at least 4 weeks following STEMI. S and SR were measured by tissue Doppler imaging individually for all myocardial segments under low-dose dobutamine stress echocardiography. Patients underwent resting 99mTc-sestamibi scintigraphy using the standard imaging technique. Based on the results of 99mTc-sestamibi scintigraphy, the dobutamine-induced S and SR were compared between viable and non-viable segments. Receiver-operating characteristics curve was constructed to determine the cutoff value of the dobutamine-induced S and SR that best identifies viability. Results: The dobutamine-induced S and SR were significantly higher in viable compared with non-viable segments, a finding that was consistent for most individual myocardial segments (10 out of 16 for S and 11 out of 16 for SR). A cutoff value ranging from -8.5 to -9.6% for the S identified viability in apical and mid- segments, whereas a cutoff value ranging from -11.5 to -21.5% identified viability in basal segments. Similarly, a cutoff value ranging from -0.5 to -1.2 s-1 for the SR identified viability in apical and mid- segments, whereas a cutoff value ranging from -1.4 to -1.7 s-1 identified viability in basal segments. Conclusions: In patients undergoing viability assessment following fibrinolytic therapy for STEMI, the dobutamine-induced S and SR were higher in viable versus non-viable segments. A cutoff value of dobutamine-induced S and SR identified viability in most individual myocardial segments.